2015
DOI: 10.1016/j.tins.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

New neurons in the adult striatum: from rodents to humans

Abstract: Most neurons are generated during development and are not replaced during adulthood, even if they are lost to injury or disease. It is firmly established, however, that new neurons are generated in the dentate gyrus of the hippocampus of virtually all adult mammals, including humans [1]. Many questions still remain, however, regarding adult neurogenesis in other brain regions and particularly in humans, where standard birthdating methods are not generally feasible. Exciting recent evidence indicates that calre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 79 publications
(125 reference statements)
1
32
0
1
Order By: Relevance
“…Moreover, our analyses highlighted a number of small molecules that are predicted to have an “anti-dorsalizing” or “ventralizing” effect, hence they would be specifically pro-neurogenic. This is of considerable translational interest, because the more ventral SVZ is more developed in humans [52], and adult neurogenesis has recently been described in the striatum [53], which is more extended than in rodents [54]. Moreover, the ventral SVZ gives rise to specific granule cells, such as those forming the Islands of Calleja [55], and our analyses identifies small molecules that may target the different factors that drive the differentiation of such specific neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our analyses highlighted a number of small molecules that are predicted to have an “anti-dorsalizing” or “ventralizing” effect, hence they would be specifically pro-neurogenic. This is of considerable translational interest, because the more ventral SVZ is more developed in humans [52], and adult neurogenesis has recently been described in the striatum [53], which is more extended than in rodents [54]. Moreover, the ventral SVZ gives rise to specific granule cells, such as those forming the Islands of Calleja [55], and our analyses identifies small molecules that may target the different factors that drive the differentiation of such specific neurons.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to the DG and SVZ, far fewer numbers of new neurons are generated in these regions during adulthood although better detection methods are likely needed (Gould, 2007; Arisi et al, 2012; Inta et al, 2015; Nacher and Bonfanti, 2015; Schoenfeld and Cameron, 2015). Furthermore, many questions remain about newborn neurons in these areas including their origin (local or SVZ) and functions (Shapiro et al, 2009; Lee and Blackshaw, 2012; Feliciano et al, 2015; Inta et al, 2015). Nonetheless, a growing number of studies have revealed that neurogenesis in at least some of these areas is subject to modulation by a variety of physiological and environmental factors including pregnancy, pup exposure and parenting.…”
Section: Effects Of Pregnancy Parenting and Pup Exposure On Neuromentioning
confidence: 99%
“…Neurons born in the wall of the third ventricle migrate to the hypothalamus and become leptin-responsive neurons [Kokoeva et al, 2005;Migaud et al, 2010;Cheng, 2013]. New neurons have also been documented in the adult striatum, amygdala, piriform cortex and neocortex, among other regions, although the conditions under which new neurons migrate to these less reported areas is debated [Bernier et al, 2002;Dayer et al, 2005;Luzzati et al, 2006Luzzati et al, , 2007Gould, 2007;Chawana et al, 2013;Ernst et al, 2014;Olaleye and Ihunwo, 2014;Inta et al, 2015;Saul et al, 2015].…”
Section: Direct Approaches To Understanding New Neuron Function: Renementioning
confidence: 99%